Young People as Agents of Sustainable Society Reclaiming the Future - Honkatukia, Päivi; Rättilä, Tiina (Youth, Young Adulthood and Society, 2023)
This book analyses young people's societal participation as a central dimension of their well-being and as vitally important to secure the sustainable future of humankind and the whole eco-social system. It develops a theoretical framework for analysing youth participation holistically, embedded in its everyday context, and as a relational phenomenon, underpinned by universal human needs. It introduces innovative methodological approaches to study youth engagements in society. This book will appeal to scholars and students of youth studies, sociology, sustainable development, youth participation and education. It also offers new knowledge and theoretical readings for policy experts on youth and sustainable development, as well as for NGOs working with youth.